Tracing the pathways and mechanisms involved in medicinal uses of flaxseed with computational methods and bioinformatics tools - Joshi, Sravani; Srivastava, Ruby (Frontiers in Chemistry, 2024)
Pharmacological drugs targeting specific pathways involved in various diseases have seen recent advancement with newer and more efficient emerging drug targets but these drugs are limited in terms of their side effects and patient adherence. The potential of plant-based diets in the form of functional foods is increasingly being realized as an option to treat and/or prevent several diseases. In this work, we have selected flaxseed (Linum usitatissimum), also known as linseed to study its pharmacological efficacy and proposed mechanisms of action for medicinal purposes. The target genes of linseed with disease specificity index (DSI > 0.6) are compared to the associated genes of diabetes mellitus, decrease in appetite, addictive behavior, cardiovascular diseases, Inflammatory Bowel Diseases (IMD), Polycystic Ovary Syndrome (PCOS) and the selected genes are evaluation further using in silico methods. The binding affinity of flaxseed to three common target proteins family (CCDC28b, PDCD6IP and USP34) is assessed by docking and Molecular dynamics (MD) simulations. Results show that linseed is safe to use for mutagenic toxicity and other cardiotoxicity measures but linseed is unsafe for embryotoxicity, herG toxicity and cardiac failure. The protein-protein interaction (PPI) network, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways analysis indicates that flaxseed can be used as a medicinal herb for diabetes mellitus, cardiovascular diseases, Inflammatory Bowel Diseases (IMD) and Polycystic Ovary Syndrome (PCOS).